PENGARUH PENAMBAHAN TEPUNG KACANG MERAH UBI JALAR UNGU TERHADAP SIFAT ORGANOLEPTIK FORMULA INSTAN MP-ASI BAYI USIA 6-12 BULAN - Lufita Devi; Eva Fitriyaningsih (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
The use of purple sweet potato and kidney beans attempts to increase the efficiency and economic value of purple sweet potato and kidney beans. One of them is the diversity of processed products from purple sweet potatoes and red beans, one of the uses for purple sweet potatoes and kidney beans is added to complementary foods. Purple sweet potatoes are high in carbohydrates and beans are good for vegetable protein. The aim of this research was to see the effect of red bean flour and purple sweet potato 10%, 20%, 30% on organoleptic properties (taste, aroma, texture and color). The research used experimental design with non factorial completely randomized design (CRD) with 3 treatments and 3 repetitions. organoleptic test (taste, aroma, texture and color) in the Food Technology Laboratory of the Department of Nutrition, Poltekkes Kemenkes Aceh. There was a significant effect of adding 10%, 20% and 30% purple sweet potato red bean flour mixture to the organoleptic properties (color, taste, aroma and texture) of MP-ASI with P-value 0.05. In terms of color, panelists preferred FII treatment (20%), in terms of taste of panelists, treatment of FI (10%), in terms of aroma, panelists preferred FII treatment (20%), in terms of panelist texture, FII treatment (20%) with somewhat favorable responses. . Conclusion, the addition of 10%, 20% and 30% red bean flour and purple sweet potato has a significant effect on the organoleptic properties (color, taste, aroma and texture) of the instant MP-ASI formula.Keywords: MP-ASI, red bean flour, purple sweet potato flour